Design and Development of a Mobile Based Reservation System for Muslims in Medan - Rindi Atika; M. Fakhriza; Muhamad Alda (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
Salon Muslimah Dina is a privately owned business offering a variety of beauty treatments specifically for women. Operationally, the salon still uses a manual system, requiring customers to visit in person or contact them via WhatsApp to make reservations or inquire about services. The high volume of inquiries slows down the service process, as the salon must respond to messages individually. Furthermore, the lack of transaction data records often results in long wait times for walk-in customers and inconsistencies in service delivery. Important information such as operating hours, service types, prices, and locations are also not communicated effectively to potential customers. To address these issues, an online reservation system was developed to disseminate information and facilitate service bookings. This system utilizes the FCFS (First Come, First Served) scheduling method, where services are processed in the order of arrival and completed one by one. This method is considered fair because the entire process is handled in the order in which they arrived. The development results demonstrate that the reservation system has been successfully developed, with features that simplify customer bookings without having to visit in person, saving time and money. This system also helps the salon manage service data, schedules, and reservation information more optimally and efficiently.